New-Onset Diabetes, Endothelial Dysfunction, and Cardiovascular Outcomes in Hypertensive Patients: An Illness-Event Model Analysis - Maio, Raffaele (Biomedicines, 2021)
Background. Insulin resistance and endothelial dysfunction are common findings in hypertensives, both predisposing to a higher risk of diabetes and cardiovascular events. We designed this study to evaluate the role of endothelial dysfunction in three pathogenetic pathways: (1) from baseline to cardiovascular events, (2) from baseline to diabetes, and (3) from new-onset diabetes to cardiovascular events. Methods. We enrolled 653 Caucasian never-treated hypertensives. Endothelial dysfunction was investigated by strain-gauge plethysmography; incident diabetes and cardiovascular events were evaluated by an illness-event model analysis. Results. During the follow-up (median 113 months), we documented 191 new cardiovascular events and 92 new cases of diabetes. In a multiple Cox regression analysis, acetylcholine-stimulated forearm blood flow [100% decrease, hazard ratio: 2.42 (95% confidence interval = 1.72–3.40)] and serum high-sensitivity C-reactive protein [hazard ratio: 1.30 (95% confidence interval = 1.21–1.40)] had an independent association with cardiovascular outcomes. The incidence rate of cardiovascular outcomes in diabetes-developer patients was higher than in the diabetes-free ones (34.9 vs. 2.5 events per 100 persons-year). In an illness-event model, a 100% decrease in forearm blood flow was associated with a 55.5% hazard ratio increase (hazard ratio: 1.56, 95% confidence interval: 1.33–1.82) of transition 1 (from baseline status to cardiovascular events) and to an almost doubled increase (hazard ratio: 2.54, 95% CI: 2.00–3.25) of the risk of transition 2 (from baseline status to diabetes). No such effects were found in transition 3 (from diabetes to cardiovascular events). Conclusions. Endothelial dysfunction plays a primary role in the pathways leading to diabetes and cardiovascular events in hypertensives. When diabetes is overt, endothelial dysfunction has no predictive value for subsequent cardiovascular events.